Estimation of Household Demand Systems Using Unit Value Data - Ian Preston; François Laisney; Ian A. Crawford (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1997)
We develop a method for estimation of price reactions using unit value data which exploits the implicit links between quantity and unit value choices. This allows us to combine appealing Engel curve specifications with a model of unit value determination in a way which is consistent with demand theory, unlike methods hitherto prominent in the literature. The method is applied to Czech data.
More recent version: http://hdl.handle.net/10419/24235
Keywords: D11; D12; 330; Consumer demand; unit values; quality; Verbraucherausgaben; Nachfragesystem; Mikroökonomische Konsumfunktion; Tschechische Republik